Kinetics of alpha-amylase production in a continuous culture of Bacillus licheniformis - Votruba, J; Emanuilova, E; Kaymakchiev, A; Pazlarová, J (Folia microbiologica, 1984)
As found during continuous cultivation of Bacillus licheniformis on a semisynthetic medium (glucose or maltose as C source), the specific rate of alpha-amylase production is proportional to growth rate but is repressed by higher substrate concentrations. Besides glucose or maltose, peptone was also used as an alternative carbon source during cultivation. The specific rate of production of the enzyme on maltose is half that found with glucose.
Keywords: kinetika; Bacterial Proteins; alpha-Amylases; Bacteriological Techniques; alfa-amylasy; bakteriologické techniky; bakteriální proteiny; Bacillus; Kinetics